Analysis of solar urticaria in Thai patients - Narumol Silpaarcha (2018)
© 2016, Allergy and Immunology Society of Thailand. All rights reserved. Background: Solar urticaria (SU) is an uncommon photodermatosis characterized by erythema and whealing within minutes to a few hours after exposure to sunlight or an artificial light source. Purpose: To determine the clinical features, photobiological characteristics and treatment outcomes in Thai SU patients visiting a tertiary referral hospital. Method: A retrospective analysis of 13 patients with SU was conducted. Demographic data, disease characters, phototesting results, laboratory investigations, treatment and outcome were evaluated. Results: Of the 13 patients diagnosed with SU from 2000 to 2012, most patients were female (10, 77%). The mean age of onset was 29 years (15-51). The mean duration of SU was 46 months (6-120) at presentation. The most common affected location was the upper extremities (92%), followed by head and neck (77%). The responsible action spectra were visible light in 8 patients (61.5%), ultraviolet A (UVA) in 1 patient (8%), and both visible light and UVA in 4 patients (31%). The median course from disease onset to disease resolution was 63 months (95% confidence interval 30-95). After 13 months and 55 months from the onset of symptoms, 23% and 49% of patients, respectively, were predicted to recover from their symptoms. Conclusion: Solar urticaria is a rare condition in Thailand. The common eliciting spectra of SU were visible light and UVA. Management of SU remains challenging.